Polynomial Invariants for Arbitrary Rank D Weakly-Colored Stranded Graphs - Avohou, R.C. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
Polynomials on stranded graphs are higher dimensional generalization of Tutte and Bollobás-Riordan polynomials [Math. Ann. 323 (2002), 81-96]. Here, we deepen the analysis of the polynomial invariant defined on rank 3 weakly-colored stranded graphs introduced in arXiv:1301.1987. We successfully find in dimension D≥3 a modified Euler characteristic with D−2 parameters. Using this modified invariant, we extend the rank 3 weakly-colored graph polynomial, and its main properties, on rank 4 and then on arbitrary rank D weakly-colored stranded graphs.